2020
DOI: 10.1016/j.jecp.2019.104704
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes versus intentions in fairness-related decision making: School-aged children’s decisions are just like those of adults

Abstract: The notion of what constitutes fairness has been assumed to change during childhood, in line with a marked shift from outcome-based to intention-based moral reasoning. However, the precise developmental profile of such a shift is still subject to debate. This study sought to determine the age at which the perceived intentions of others begin to influence fairnessrelated decision-making in children (aged 6-8 and 9-11) and adolescents (aged 14-15) in the context of the mini-ultimatum game. The mini-ultimatum gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Overall career selection trends and the prospective role of specialized career counseling. During adolescence, young people make critical decisions (Featherman, 1980;Duryea et al, 2003;Jaroslawska et al, 2020). Our survey results at Sapporo Kaisei Secondary School show that the adolescents who have already decided about their career paths are strongly influenced by jobs in science and technology (around 76% want to join this field).…”
Section: Discussionmentioning
confidence: 81%
“…Overall career selection trends and the prospective role of specialized career counseling. During adolescence, young people make critical decisions (Featherman, 1980;Duryea et al, 2003;Jaroslawska et al, 2020). Our survey results at Sapporo Kaisei Secondary School show that the adolescents who have already decided about their career paths are strongly influenced by jobs in science and technology (around 76% want to join this field).…”
Section: Discussionmentioning
confidence: 81%
“…Overall, however, 6-to 7-year-olds clearly showed that they are able to consider what characters could have chosen to do. It seems likely that 6-to 9-year-old children were inferring the intentions of the characters based on the choices that were available to them (as in Jaroslawska et al, 2020;Pesowski et al, 2016;Zhao et al, 2021). That is, when a character had a choice, children could be more certain that they intended to either be mean or nice, whereas when characters did not have a choice, children could not be sure of their intentions.…”
Section: Gen Er a L Discussionmentioning
confidence: 99%
“…There is some evidence that children make judgments of fairness based partly on the choices someone had available to them (Jaroslawska et al, 2020; Sutter, 2007). For example, Jaroslawska et al (2020) asked children aged 6–8 years to judge the fairness of an offer from a proposer in the context of a mini‐ultimatum game.…”
mentioning
confidence: 99%
“…By contrast, if P proposes an unfair offer (8P/2R) but the only other alternative was the same unfair offer (8P/2R), participants will likely infer that P's offer does not signal a bad intention. Consistently, children and adults tend to reject OUTCOME-BASED PUNISHMENT 5 the intended unfair offer in a (8P/2R-5P/5R) trial but tend to accept the unintended unfair offer in a (8P/2R-8P/2R) trial (Falk et al, 2003;Jaroslawska et al, 2020;Radke et al, 2012).…”
Section: An Outcome Bias In Older Adults' Socio-economic Decisionsmentioning
confidence: 94%